A study of the function of carotenoid pigments of a red psychrophilic micrococcus from Antarctica - Minogue, Lucy Lancaster (Virginia Polytechnic Institute and State University, 1972)
A red psychrophilic micrococcus (Strain VPI20A) which was isolated from Antarctic Dry Valley soils was used in this investigation to determine the culture's sensitivity to ultraviolet radiation (180 to 300 nm). The spectrum of the typically pigmented culture showed that absorption maxima occurred at 210, 260, 320, 370, 390, 445, 465, 495 and 530 nm, with major maxima at 465, 495 and 530 nm, indicating presence of lycopene or other related compounds. Spectra from a white phenotype which had carotenogenesis suppressed by diphenylamine indicated maxima only in the ultraviolet range (390 nm and below). Comparative sensitivities of red and white cells to ultraviolet radiation were determined with cultures which had been harvested in both log and stationary phases. In the stationary phase, both types of cells had similar mortality curves. The stationary phase cultures were more sensitive than those of the log phase. However, log phase cells had differing death curves, with pigmented cells exhibiting greater resistance to ultraviolet radiation than nonpigmented cells. Addition of amino acids to the growth medium and changes in incubation temperature did not enhance or decrease carotenogenesis, and ascorbate, fluoride, methylene blue, cyanide, azide and glutathione did not affect synthesis of carotenoids in the concentrations used. M.S.